Research on the mechanism of cow milk protein dietary intervention in ameliorating systemic chronic inflammation in type 2 diabetes by disrupting the ROS-M1 macrophage axis - Zhang, Fumei; Bai, Lin; Yang, Heqiang; Yang, Jianrong; Sun, Zhuxin; Wei, Jia; Qiao, Zilin; Wei, Yumei; Song, Fei; Tian, Xiaojing; Hu, Xiaoxia (Frontiers in Nutrition, 2026)
IntroductionRecent studies suggest that type 2 diabetes mellitus (T2DM) is characterized by a systemic, low-grade chronic inflammatory state. Although cow milk protein (CMP) has been shown to alleviate this inflammation, its underlying mechanisms remain unclear.MethodsTherefore, we investigated how CMP mitigates systemic chronic inflammation in T2DM using both in vitro digestion and mouse models.ResultsThe in vitro digestion model demonstrated that CMP, with its low degree of hydrolysis, exhibits significant anti-α-amylase and antioxidant activities. In the in vivo study, CMP markedly reduced fasting blood glucose (FBG) and reversed diabetes-related body weight loss. CMP intervention significantly decreased oxidative stress markers, including malondialdehyde (MDA) and reactive oxygen species (ROS), while enhancing the activity of the antioxidant enzyme glutathione peroxidase (GSH-Px). Moreover, CMP suppressed macrophage polarization toward the M1 phenotype and reduced the levels of pro-inflammatory cytokines. Finally, CMP administration ameliorated lipid infiltration in the liver and intestine, mitigated pancreatic islet atrophy, and concurrently alleviated renal pathologies such as glomerular hypertrophy, glycation, and fibrosis.DiscussionIn conclusion, CMP ameliorates systemic chronic inflammation in T2DM by disrupting the ROS–M1 macrophage vicious cycle.